Pengaruh model project based learning dan minat belajar terhadap keterampilan menulis teks prosedur peserta didik kelas v di sekolah dasar - Putri Amalia Ramadhani; St Y Slamet (Didaktika Dwija Indria, 2025)
This research investigated how different instructional approaches and levels of student interest impact procedural writing skills. Specifically, it examined: (1) the comparative effectiveness of Project-Based Learning (PjBL) versus Problem-Based Learning (PBL) in enhancing writing performance; (2) the influence of varying degrees of learning interest on students' writing outcomes; and (3) whether a combination of instructional model and interest level produces any interaction effects. Adopting a 2×2 factorial design within a quantitative quasi-experimental framework, the study involved 50 fifth-grade students from public elementary schools in Argomulyo Subdistrict, selected through cluster random sampling. Instruments used included procedural writing assessments and interest-in-learning questionnaires, with data analyzed using Two-Way ANOVA. The results demonstrated that the type of instructional model significantly affected students’ writing abilities (FA = 4.221 > Ftable = 4.06), as did learning interest (FB = 47.211 > Ftable = 4.06); however, no significant interaction was found between the two variables (FAB = 0.017 < Ftable = 4.06).These findings indicate that both the PjBL model and learning interest independently affect students’ procedural writing skills. The implication, theoretically, it strengthens the idea that project-based learning effectively enhances writing skills through meaningful and collaborative experiences. Practically, it implies that teachers can implement the Project Based Learning model to foster students’ interest and improve their ability to write procedural texts in a creative and structured manner.